IMPLEMENTASI NILAI PANCASILA OLEH PARTAI POLITIK DI PROPINSI RIAU DALAM MEMBANTU MASYARAKAT TERDAMPAK BENCANA TAHUN 2019-2020 - Adlin Adlin (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2020)
This paper aims to describe the implementation of the values of Pancasila by political party cadres in the Riau Province in the form of mutual cooperation to help victims affected by the 2019-2020 disaster. Using qualitative methods with documentation data collection techniques from various related sources. After the data has been collected, data reduction, data presentation and conclusion drawing are performed. The results showed that cadres of political parties practiced mutual cooperation to help communities affected by disasters in accordance with Pancasila teachings. During the haze disaster in 2019, political parties in Riau opened health posts in 12 city districts with complete facilities and even political party offices became places of refuge for residents of victims of the haze disaster. During the Covid-19 disaster, political party cadres who held positions helped the community by donating their salaries, providing basic necessities, personal protective equipment to the community.